Perceived security towards e-banking services: an examination among Malaysian young consumers - Zaiton Osman; Azaze @ Azizi Bin Haji Abdul Adis; Grace Phang (Penerbit UMS, 2017)
Electronic banking (or e-banking) has experienced an exponential growth in Malaysia in the recent years. It transforms the traditional banking services and leads to a huge shift in global marketing practices. Despite its popularity, many consumers still doubt about its efficiency and effectiveness. This paper aims to examine how young consumers, especially the Generation Y, perceive the e-banking security based on their perceived regulatory related issues, protected transaction, adequate mechanism and service quality. The results showed that all independent variables, except adequate mechanism, were significantly related to the perception of e-banking security. The findings provide important insights to both academicians and e-banking practitioners in planning for their e-banking strategy.